Analysis of Speech-Sign Semantic Equivalence in Simultaneous Communica tion in Kenya - Peter Oracha, Adoyo (2017)
Effective communication between teacher and pupil is a requisit e factor for educational attainment. For the deaf, ineffective communi cation is a major problem especially when onset of profound deafness t akes places at an early age before language is acquired. At school, th e language of classroom communication not only affects the child’s dev elopment but also influences ability to learn other curriculum content s. Pointing out reasons for failure by deaf children to compete favora bly with their hearing peers, Johnson et al (1989) has indicated that the central problem on deaf education is embedded in the lack of an ap propriate language of classroom communication. For a l ong time education for the deaf was conducted through the oral approac h. It was later realized that this oral approach did not avail curricu lum content to the deaf learners. In the 1980’s Total Communication ar ose as one of the solutions. According to Adoyo (2004), Total Communic ation was misunderstood for Simultaneous Communication, a communicatio n system in which speech and sign are produced at the same time (Lane, Hoffmister & Bahan, 1996). Although SC has been used in Kenya for all these years, it has not produced the predicated large-scale impro vement. In this study, an attempt was made to establis h the capacity of SC to enhance understanding and to facilitate inform ation processing. The investigation was carried out through an examina tion of the extent to which the spoken and signed messages were equiva lent in meaning. The research question was: To what extent do teachers of the deaf maintain one-one, sign to-voice ratio during Simultaneous Communication transmission and to what degree is the spoken and signe d message equivalent semantically?